Licensing with free entry - Toker Doganoglu; Firat Inceoglu; Johannes Muthers (Johannes Kepler University of Linz, Department of Economics, 2018)
We introduce a fairly general licensing model with an endogenous industry structure - in terms of number of active firms - and general licensing contracts. We show that when the patentee can employ contracts that can condition on market entry or price, it can implement an outcome that yields monopoly profits by awarding the license to a single firm. Furthermore, when the patentee can only use contracts based on the quantities of the licensees, it still captures the entire market via a single licensee, albeit not at the monopoly price. Commonly assumed two-part tariff contracts cannot duplicate this last outcome and yield lower profits. We discuss the welfare implications of various contractual schemes.
Keywords: D45; K11; L11; L13; L21; L41; 330; Patent licensing; free entry; quantity competition